A COMPUTERIZED FORECASTING SYSTEM FOR STUDENT ENROLLMENT IN KFUPM - Pulak, M.F.S. (2020)
ABSTRACT. Any higher education institute like a university should have a tentative future plan. The first step in establishing such a plan is to get the required information concerning the projected student enrollment for the next few years. Though an enrollment forecasting is a specific type of estimation - one that uses past information in some manner to arrive at an estimate of future enrollments. The basic assumptions are that some historical pattern exists, that this pattern can be identified and data can be collected to measure it, and that it reflects what is it to occur in the future. In this paper, we will show a systematic analysis of students data to identify the hidden historical pattern and its important parameters which is essential for the forecasting. A computer program will be developed based on that historical pattern. The computer program then can be used as a powerful simulation tool to project the future enrollment.